2012
DOI: 10.1111/j.1553-2712.2012.01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Medical Student Selection of an Emergency Medicine Residency Program: Implications for Training Programs

Abstract: Objectives: An understanding of student decision-making when selecting an emergency medicine (EM) training program is essential for program directors as they enter interview season. To build upon preexisting knowledge, a survey was created to identify and prioritize the factors influencing candidate decision-making of U.S. medical graduates.Methods: This was a cross-sectional, multi-institutional study that anonymously surveyed U.S. allopathic applicants to EM training programs. It took place in the 3-week per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 9 publications
4
78
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20] The interview may also identify negative applicant characteristics such as anxiety or aggression. 21 Candidates value the interview process highly, 22,23 and cite the quality of interactions with the program director 24 and, most important, with the residents [25][26][27] during the interview as important in their decision making. Applicants value the interaction with residents during an interview to assess resident morale, 28 esprit de corps, 29 and program ''red flags'' as perceived by applicants.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] The interview may also identify negative applicant characteristics such as anxiety or aggression. 21 Candidates value the interview process highly, 22,23 and cite the quality of interactions with the program director 24 and, most important, with the residents [25][26][27] during the interview as important in their decision making. Applicants value the interaction with residents during an interview to assess resident morale, 28 esprit de corps, 29 and program ''red flags'' as perceived by applicants.…”
Section: Introductionmentioning
confidence: 99%
“…Five of these articles appeared in our highlighted section, but for each one of those featured, this metric was a secondary outcome measure. 18,33,41,45,46 Pediatric topics accounted for nine (19%) of the articles reviewed. [20][21][22]24,40,41,55,56,58 The two that are in the highlighted section used technology as the basis of their studies, and both received funding.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
“…The sources of funding were as follows: five federal (two NIH, one Canada, and one Taiwan), five universitysponsored, two industry-supported, and two organizationally funded. Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…3 A survey of EM training applicants identified geographic location and program characteristics including, but not limited to, influences such as reputation of the program, length of the program, interview experience, and personal experience with residents as priorities. 4 Levine et al 5 interviewed female medical students and found that sex seems to play a role, albeit complex, in how female medical students look at a residency mentoring relationship. Respondents in this study also identified a need for access to female mentors.…”
mentioning
confidence: 99%